CROSSED CATEGORIZATION RESTRICTIONS WITH ATYPICAL CROSSING OF CATEGORIES:THE AFFECTIVE STATE IMPACT - Ramírez de la Fe, Mª del Carmen; Rodríguez Pérez, Armando; Rodríguez González, Ángel (Anales de Psicología / Annals of Psychology, 2006)
An aspect that has hardly ever been considered in crossed categorization is the crossing typicality used to obtain the intergroup bias reduction. With regard to this subject, Eurich-Fulcer y Schofield (1995) have found that when correlated categories are crossed (typical crossing of categories), intergroup bias increases, instead of decreasing. The consequences of the affect that can arise in the face of the atypical crossing of categories are analysed in this study. Based on Forgas studies (1992), we predict that affect is going to influence the impression formation about subjects with atypical crossing of categories more than about subjects with typical crossing of categories. Results confirm our predictions. This effect can involve a problem in the use of crossed categorization for the intergroup relations improvement. Since the affect generated by persons belonging to unknown or strange outgroups is normally negative, atypical crossing of categories can also promote the production of negative impressions.